Lifetime Risk of Venous Thromboembolism in Two Cohort Studies - Bell, Elizabeth J; Lutsey, Pamela L; Basu, Saonli; Cushman, Mary; Heckbert, Susan R; Lloyd-Jones, Donald M; Folsom, Aaron R (The American journal of medicine, 2016)
Greater public awareness of venous thromboembolism may be an important next step for optimizing venous thromboembolism prevention and treatment. "Lifetime risk" is an easily interpretable way of presenting risk information. Therefore, we sought to calculate the lifetime risk of venous thromboembolism (deep vein thrombosis or pulmonary embolism) using data from 2 large, prospective cohort studies: the Cardiovascular Health Study (CHS) and the Atherosclerosis Risk in Communities (ARIC) study. We followed participants aged 45-64 years in ARIC (n = 14,185) and ≥65 in CHS (n = 5414) at baseline visits (1987-1989 in ARIC, 1989-1990 and 1992-1993 in CHS) for incident venous thromboembolism (n = 728 in ARIC through 2011 and n = 172 in CHS through 2001). We estimated lifetime risks and 95% confidence intervals of incident venous thromboembolism using a modified Kaplan-Meier method, accounting for the competing risk of death from other causes. At age 45 years, the remaining lifetime risk of venous thromboembolism in ARIC was 8.1% (95% confidence interval, 7.1-8.7). High-risk groups were African Americans (11.5% lifetime risk), those with obesity (10.9%), heterozygous for the factor V Leiden (17.1%), or with sickle cell trait or disease (18.2%). Lifetime risk estimates differed by cohort; these differences were explained by differences in time period of venous thromboembolism ascertainment. At least 1 in 12 middle-aged adults will develop venous thromboembolism in their remaining lifetime. This estimate of lifetime risk may be useful to promote awareness of venous thromboembolism and guide decisions at both clinical and policy levels.